Design of Ultrahigh Energy Resolution RIXS Beamline at NanoTerasu. Issue 1 (1st December 2022) - Miyawaki, Jun; Fujii, Kentaro; Imazono, Takashi; Horiba, Koji; Ohtsubo, Yoshiyuki; Inami, Nobuhito; Nakatani, Takeshi; Inaba, Kento; Agui, Akane; Kimura, Hiroaki; Takahasi, Masamitu
Abstract: The optical design of the ultrahigh-resolution RIXS beamline, which is currently developed at NanoTerasu in Japan, is described. The main goal of this beamline is to perform ultrahigh-resolution RIXS measurements with a total energy resolution of <10 meV at 250–1000 eV with E /Δ E >150, 000 for both beamline and RIXS spectrometer. To achieve the ultra-high resolution, a 2D-RIXS spectrometer using energy-dispersive X-ray is employed to compensate for lower throughput at higher energy resolution, and the optics of the beamline is optimized for the 2D-RIXS spectrometer. A vertically dispersing in-focus variable-included-angle varied-line-spacing plane grating monochromator is employed for the beamline, with an entrance slit to ensure the ultrahigh resolution. First and second mirrors focus X-ray on entrance slits vertically and horizontally, respectively, and the divergent X-ray is irradiated onto the grating. For the 2D-RIXS spectrometer, there is no exit slit, and the vertically energy-dispersed X-ray is irradiated directly onto a sample. In front of the sample, X-ray is horizontally refocused by a Wolter type-I mirror. The expected horizontal focus size at the sample is 0.7 μm. The expected photon flux is 1×10 11 photons/s at 500–1000 eV with a virtual slit width of 2 μm required for E /Δ E >150, 000. The height of the dispersed X-ray available in the 2D-RIXS spectrometer is 120 μm, which allows the use of a remarkably high flux of 6×10 12 photons/s, and the beamline will serve as an ultrahigh-resolution and high-efficiency RIXS facility.